An experimental investigation on delamination factor and thrust force evaluation of kenaf fiber and acacia concinna filler reinforced epoxy hybrid composites - Chiranjeevi Pachappareddy; Chinmaya Prasad Padhy; Srinivas Pendyala (Green Technologies and Sustainability)
This study investigates the delamination factor and thrust force in chemically treated kenaf fiber reinforced composites (KFRC) hybridized with different percentages of acacia concinna fillers. Natural fibers and fillers have garnered significant attention for their composite materials use due to their favorable environmental attributes and capacity to improve mechanical properties. Kenaf fiber surfaces are chemically treated with 6% NaOH to remove the hemicellulose and lignin on the fiber surface, improving the adhesive bonding between fiber and matrix. In this study, kenaf fiber, known for its lightweight, quick growth, economic, and high tensile strength, is combined with different percentages of acacia concinna natural fillers and epoxy polymer to enhance the performance of composites. The delamination factor and thrust force, critical parameters influencing composites’ durability and structural integrity, are analyzed to understand the effects of filler percentage on interlaminar properties. Drilling parameters were also considered, including speed, feed, and drill bit material. ANOVA has been used to determine the parameter that significantly affects the delamination factor and thrust force. Delamination and thrust force are minimal on the surface of the drilled hole at 500 rpm speed, 50 mm/min feed, carbide with TiN coated drill bit material, and no filler.